Water Quality of Lamong River in Gresik Regency Based on Phytoplankton Diversity and Chemical Physics Factors - Firmansyah, M. Ryan Aries Firmansyah; Wisanti, Wisanti (LenteraBio : Berkala Ilmiah Biologi, 2025)
Lamong River is included in the Bengawan Solo River area. Its upstream part is in Lamongan and Mojokerto regencies, while its downstream part is in Gresik regency. Along the Kali Lamong river there are many human activities, such as irrigation, industry, agriculture, and others, which can cause water pollution. Phytoplankton is an aquatic organism that can be used as an indicator of water quality in a body of water. This study aims to analyze the water quality of Lamong River in terms of phytoplankton diversity and chemical physical factors. Sampling was conducted in Lamong River at 3 stations with 3 points and 3 repetitions in the form of phytoplankton samples and water samples. Phytoplankton data was calculated with Shannon-Wiener diversity index. Chemical physics data were analyzed using chemical physics water quality test technique. Correlation of phytoplankton diversity index and physico-chemical factors of water quality using SPSS ver.22.00. The results showed that in the waters of Lamong River, phytoplankton were found that belonged to 5 divisions, 12 families, and 13 species. The phytoplankton diversity index of 2.40 was categorized as moderate. The water quality of Kali Lamong is included in the good criteria, because overall the physico-chemical factors meet the water quality standards. The diversity index showed a negative correlation with pH, and a positive correlation with DO, BOD, temperature, and turbidity. The DO parameter has the highest positive correlation showing a strong correlation with the phytoplankton diversity index of +0.687. Based on physico-chemical indicators, it can be concluded that the waters of Kali Lamong are not yet polluted.